ANALISIS ISI KOLOM HIKMAH PADA HARIAN REPUBLIKA - Syahir Syahir (Wardah, 2011)
General daily Republika characteristics as Islamic-based national newspaper. Wisdom column on the first page of the paper on the progress of orientation marks nerupakan Islam. The research was conducted, the first to know Wisdom column from the aspect of content analysis. The second mission to find the essence of the wisdom contained in the column daily Republika general, be formulated as follows: First how content analysis of newspaper columns on the general wisdom of Republika?. Both how the essence of propaganda is contained in the general field Republika daily lessons?, Perspective is descriptive qualitative approach. Analysis of the data using content analysis aimed to describe and include comparison of the content of media, load ratio between the content of media and social reality. Based on the results of analyzes done on the contents of the "Wisdom" in general Replublika published daily from June 1 to May 31, 2011 themes that dominate the appearance and quantity is about morality. Next, followed by the theme of Islamic creed and last theme. The essence of his message lies in the character of its institutional mission and vision.